Ayurvedic Management of Psoriasis - Bishnoi, Vimla; Rajoria, Kshipra; Singh, Sarvesh Kumar; Bhoomika (International Research Journal of Ayurveda & Yoga, 2024)
Plaque psoriasis, akin to Mandalakhushta in Ayurveda, presents as scaly lesions and persistent rashes, often resistant to therapy. While topical corticosteroids may provide temporary alleviation, they do not address the underlying causes of the condition. Top of Form A 24-year-old male student, with symptoms aligning with Mandalakhustha, exhibited redness, scaling, and itching across his limbs and trunk for a month. The assessment identified Vata and Kapha as the involved Doshas. Diagnosis verification through biopsies can be confirm for plaque psoriasis, leading to conventional Kushta treatment. Pre-operative therapies, such as Rukshana (dehydration therapy) and Snehapana (medicinal ghee consumption), were followed by Vamana (emetic therapy) and Virechana (purgative therapy). The treatment spanned a month, supplemented by the Sansarjana Karma diet. Combining Shaman and Shodhan Chikitsa within Panchkarma therapy, along with internal medicine, yielded satisfactory results in this study.